Islamic Education Overcoming Social Conflicts in Society in the 5.0 Era: An Analysis of Nurcholish Madjid's thoughts (Cak Nur) - Nuha, Muchammad Ulin; Fihris, Fihris; Astuti, Nita Yulia (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study examine the relevance of Nurcholish Madjid's thinking to overcome social conflicts in the digital era 5.0. In the context of an increasingly polarized Indonesia due to the spread of inaccurate information and digital inequality, Madjid's thinking on inclusive Islam offers a relevant solution. By emphasizing the values of pluralism, tolerance, and interfaith dialogue, Madjid's thinking can be the foundation for a more inclusive Islamic education. This study uses a literature study method to analyze the works of Madjid and related literature that are primary and secondary sources in this study. The results of the study show that Madjid's thinking can be an important reference in formulating Islamic education strategies that are able to foster mutual respect and reduce potential conflicts. Thus, Islamic education can play a role as an agent of social change that is able to create a more harmonious and peaceful Indonesian society. It is hoped that this article can provide views for educators to implement inclusive educational approaches and strategies to achieve the goals of Islamic education.